2007
DOI: 10.1590/s1517-83822007000200024
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Listeria monocytogenes in low acid italian sausage produced under brazilian conditions

Abstract: Dry sausages have been considered ready-to-eat products with low risk of causing listeriosis due to the hurdles created during the manufacturing process such as low pH and aw, high salt concentration and presence of lactic acid bacteria (LAB). However, several studies have detected survival of Listeria monocytogenes in these products and also shown that process parameters, LAB and L. monocytogenes strains directly influence the results. In this work, survival of the pathogen in sausages prepared with three dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 24 publications
(39 reference statements)
4
9
0
Order By: Relevance
“…1). This is in agreement with published works investigating the in situ nonthermal inactivation of the pathogen during manufacturing of fermented sausages (Degenhardt & Sant' Anna, 2007;Drosinos et al, 2006;Gareis, Kabisch, Pichner, & Hechelmann, 2012;Mataragas, Bellio, Rovetto, Astegiano, Decastelli, et al, 2014;Submitted for publication;Mataragas, Bellio, Rovetto, Astegiano, Greci, et al, 2015). In those studies the inactivation curve varies between linear and various shapes of a non linear pattern indicating the potential presence of a more resistant subpopulation due to stress adaptation.…”
Section: Modeling L Monocytogenes Inactivation During Storage and Pasupporting
confidence: 91%
“…1). This is in agreement with published works investigating the in situ nonthermal inactivation of the pathogen during manufacturing of fermented sausages (Degenhardt & Sant' Anna, 2007;Drosinos et al, 2006;Gareis, Kabisch, Pichner, & Hechelmann, 2012;Mataragas, Bellio, Rovetto, Astegiano, Decastelli, et al, 2014;Submitted for publication;Mataragas, Bellio, Rovetto, Astegiano, Greci, et al, 2015). In those studies the inactivation curve varies between linear and various shapes of a non linear pattern indicating the potential presence of a more resistant subpopulation due to stress adaptation.…”
Section: Modeling L Monocytogenes Inactivation During Storage and Pasupporting
confidence: 91%
“…Evidence for the L. monocytogenes inactivation during production and cold storage of fermented sausages has been documented (Byelashov et al, 2009;Degenhardt and Sant' Anna, 2007;Drosinos et al, 2006;Farber et al, 1993;Foegeding et al, 1992;Gareis et al, 2012;Gounadaki et al, 2007;Lahti et al, 2001;Mataragas et al, 2015aMataragas et al, , 2015bMataragas et al, , 2015cMataragas et al, , 2015dPorto-Fett et al, 2008;Simpson et al, 2008;Thevenot et al, 2005) and the meta-analysis confirmed this effect, but it provided also a quantitative estimation of the overall effect of these processes on L. monocytogenes survival in the fermented sausages. Meta-analysis is a powerful statistical method analyzing a relatively large amount of data from different individual studies with different experimental designs to produce a more precise with greater statistical power estimate of a particular intervention/treatment or to identify sources of variation (Gonzales-Barron et al, 2008).…”
Section: Meta-analysis Of the In Situ L Monocytogenes Behavior Durinmentioning
confidence: 96%
“…This represents the best scenario (baseline) for sausage production characterized by good raw material pH and a w values and optimal fermentation. Degenhardt and Sant'anna (2007a); Cirolini et al (2010) .…”
Section: G1mentioning
confidence: 99%
“…During maturation, the fermentation and drying conditions vary depending on the product quality and the culture ( Degenhardt and Sant'anna, 2007a;Hutkins, 2006 ). The fermentation and drying conditions applied here were 72 h at 24 °C, 72 hours at 20 °C and 18 days of drying at 14 °C, resulting in 24 days of maturation in total.…”
Section: Fermentation and Drying Process (Survival Model)mentioning
confidence: 99%